Health Screening as a Promotive and Preventive Effort for Non-Communicable Diseases - Ika Silvitasari; Wahyuni Wahyuni; Hermawati Hermawati (Urecol Journal. Part F: Community Development, 2021)
Based on the 2018 RISKESDAS, it was reported that the prevalence of the number of non-communicable diseases (PTM) was still very high, the prevalence of diabetes mellitus in DI Yogyakarta reached 2.4%, which is second only to DKI Jakarta. The prevalence of other PTM diseases such as hypertension in DI Yogyakarta reached 10.68%, cholesterol suffered a lot in the 55-64 years age group and gout in Indonesia according to medical diagnosis reached 11.9%. PTM sufferers can find out their health condition through routine health screening. This screening can be done for prevention and control of PTM. The target and output of this activity are the people in the Panjangrejo village area with the outputs in the form of tests of blood pressure, blood sugar, uric acid and cholesterol. The implementation method used by conducting health education related to PTM with LCD media and leaflets, as well as checking blood pressure, blood sugar, uric acid and cholesterol. The results of the implementation of the activity showed that there was an increase in public knowledge regarding PTM after health education was carried out. The screening results found 11 people had mild hypertension, 19 people had hyperuresemia, and 6 people were hyperglycemic, and 9 people had high cholesterol levels. Health screening is needed for residents to find out their health conditions and this activity should be carried out routinely in collaboration with health services such as the local Puskesmas.